Influence of Instagram Social Media Marketing on Brand Awareness at Kumon Puri Kencana in 2025 - Muhammad Quinadzan Al Fajr Syam; Leni Cahyani (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of marketing through Instagram on brand awareness at Kumon Puri Kencana Learning Center in 2025. Instagram, a strategic, visual-based platform with interactive features such as Stories, Reels, and IGTV, is considered capable of strengthening the relationship between brands and audiences and significantly increasing content appeal. This study used a quantitative approach with descriptive methods, and data collection techniques through questionnaires distributed to 100 active Instagram users. The variables measured included visual content quality, posting frequency, Instagram feature utilization, and follower interaction. Meanwhile, brand awareness was analyzed based on indicators of brand recognition, brand recall, and top-of-mind. The analysis showed that Instagram had a positive and significant influence on Kumon Puri Kencana's brand awareness. Simple linear regression results indicated that Instagram usage directly increased brand awareness, with 88.4% of respondents choosing Kumon as their primary tutoring center. This research contributes to the development of literature in the field of digital marketing, particularly in the education sector, and serves as a strategic reference for other educational institutions in optimizing social media as a tool to increase brand awareness.